Between conformity and individuality: Psychologists in Czechoslovakia during normalization (1968-1989) - Šikl, Radovan; Preiss, Marek; Hoskovcová, Simona (History of psychology, 2024)
The study examines the development of psychology in former Czechoslovakia during the period of "normalization" (1968-1989) and the challenges it faced under the communist regime. The restricted connection to Western psychology and the regime's control over all aspects of human activity negatively influenced the continuity of development in psychology. The regime demanded conformity, leaving individuals, including psychologists, in recurring states of internal conflict and intellectual discomfort when deciding how much to compromise in their personal and professional lives. The study identifies three groups of psychologists based on their adaptability to regime demands. The first group consists of those who aligned themselves with the regime, allowing them to hold positions of leadership and shape the conceptualization of the field. The second group comprises individuals who actively opposed the regime, facing significant limitations in their educational and career opportunities, and mostly being forced to leave the profession. The third group of psychologists belongs to the apolitical gray zone. A significant portion of individuals in this largest group passively complied with established norms and constraints, accepting the restrictions imposed on the development of Czechoslovak psychology. Fortunately, thanks to the persistent efforts of the proactive members of the gray zone and their willingness to endure significant discomfort, an even deeper decline of psychology during the normalization period was prevented. The study provides insights into the topics of education, research, Western influences, and adaptation to the communist regime within Czechoslovak psychology, illuminating the intricacies of living in that historical period. (PsycInfo Database Record (c) 2024 APA, all rights reserved).
Keywords: Czechoslovakia; Communism; Individuality; psychologie; Československo; Humans; lidé; Social Conformity; komunismus; History, 20th Century; dějiny 20. století; individualita; Psychology; sociální konformita